2022
DOI: 10.1038/s41419-022-04925-3
|View full text |Cite
|
Sign up to set email alerts
|

The aspartyl protease DDI2 drives adaptation to proteasome inhibition in multiple myeloma

Abstract: Proteasome inhibitors, such as bortezomib, are first-line therapy against multiple myeloma (MM). Unfortunately, patients frequently become refractory to this treatment. The transcription factor NRF1 has been proposed to initiate an adaptation program that regulates proteasome levels. In the context of proteasome inhibition, the cytosolic protease DDI2 cleaves NRF1 to release an active fragment that translocates to the nucleus to promote the transcription of new proteasome subunits. However, the contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Several studies found that the knockout of DDI2 sensitizes cells to proteasome inhibitors [11,12,21,22,31]. This was further interpreted as supportive of a role for DDI2-dependent recovery in the de-sensitization of cells to PI-induced apoptosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies found that the knockout of DDI2 sensitizes cells to proteasome inhibitors [11,12,21,22,31]. This was further interpreted as supportive of a role for DDI2-dependent recovery in the de-sensitization of cells to PI-induced apoptosis.…”
Section: Discussionmentioning
confidence: 91%
“…This activity recovery may explain discrepancies between robust activity against cell lines derived from various cancers, continuously treated with Btz (www.carcerrxgene.org) [6], and a lack of clinical efficacy except in MM and MCL. In addition, recovery of activity has recently been implicated in PI resistance in MM [12].…”
Section: Introductionmentioning
confidence: 99%
“…Gene knockout (KO) cell lines were generated by viral transfection of LentiCRISPR-v2 vector (Addgene reference: 52,961) containing the target single guide RNA (sgRNA) sequence as described in ( Op et al., 2022 ). The sgRNA sequence of the Luciferase gene was used as control and denominated as Cr-luci cell line.…”
Section: Methodsmentioning
confidence: 99%
“…Supporting these findings, neuron-specific Nrf1 deletion led to mice exhibiting neurodegeneration disease accompanied by the accumulation of ubiquitinated proteins (hereafter referred to as Ub-proteins) due to the reduced proteasome activity 12,13 . Importantly, the proteasome bounce-back response exhibits significant medical relevance because therapeutic proteasome inhibition by bortezomib promptly triggers the upregulation of proteasome genes in cancer cells, such as multiple myeloma cells, leading to cancer cell resistance to anticancer drugs [14][15][16][17][18][19] . Nevertheless, whether NRF1 enhances other protein degradation systems, such as autophagy, when proteasome activity is fully suppressed is unclear.…”
Section: Introductionmentioning
confidence: 99%